Handbook of Quality of Life in Cancer - Kassianos, Angelos P. (My University, 2022)
Quality of life is an important outcome when treating a cancer patient. Research is vast on the role of quality of life on patients' general wellbeing, responsiveness to treatment, and even mortality. On the other hand, there are several methodological considerations when planning to measure and assess quality of life in cancer patients. This handbook – with authorship that is diverse in terms of perspectives, countries, and fields – aims to fill a gap in the available literature and responds to a number of questions in its 26 chapters: What is quality of life and health-related quality of life and why are they important? How is quality of life assessed? What are the theoretical and methodological considerations when using quality of life outcomes in cancer research? How is quality of life useful in routine clinical care? How is quality of life impacting different cancer populations in terms of site of the cancer, age, gender, and context? Handbook of Quality of Life in Cancer is a learning and consulting tool that can be used by a diverse audience. It is an essential resource for researchers who wish to use quality of life assessment tools in clinical trials or other types of studies; clinicians who want to develop their understanding of how they can utilize quality of life and how it is important for the patients they care for; and commissioners who wish to see why quality of life may impact population health and health system costs. Students in diverse fields of study (medicine, nursing, psychology, social work, medical sociology, population health, epidemiology, and medical statistics, among others) also would benefit from using the handbook for their studies and for their continuing professional development.
Keywords: Cancer patients; Cancer research; Cancer survivorship; Epidemiology; Healthcare costs; Medical education